2017
DOI: 10.1038/onc.2017.159
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation variations are required for epithelial-to-mesenchymal transition induced by cancer-associated fibroblasts in prostate cancer cells

Abstract: Widespread genome hypo-methylation and promoter hyper-methylation of epithelium-specific genes are hallmarks of stable epithelial-to-mesenchymal transition (EMT), which in prostate cancer (PCa) correlates with castration resistance, cancer stem cells generation, chemoresistance and worst prognosis. Exploiting our consolidated 'ex-vivo' system, we show that cancer-associated fibroblasts (CAFs) released factors have pivotal roles in inducing genome methylation changes required for EMT and stemness in EMT-prone P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 81 publications
6
80
0
Order By: Relevance
“…Cancer‐associated fibroblasts (CAFs) are spindle‐shaped fibroblast‐like interstitial cells expressing α‐smooth muscle actin (α‐SMA), constitute a primary fraction of the carcinoma stroma, and are frequently exposed to different inflammatory cells and mediators in the TME . Thus, they may obtain new features that are not present in conventional fibroblasts, and these features tend to mediate reshaping of the TME and ultimately impact cancer evolution . CAFs have an active role in mutual bidirectional interactions with tumor cells and other cell types in the TME, thereby promoting the niche that allows the tumor and promoting tumor development.…”
Section: Introductionmentioning
confidence: 62%
“…Cancer‐associated fibroblasts (CAFs) are spindle‐shaped fibroblast‐like interstitial cells expressing α‐smooth muscle actin (α‐SMA), constitute a primary fraction of the carcinoma stroma, and are frequently exposed to different inflammatory cells and mediators in the TME . Thus, they may obtain new features that are not present in conventional fibroblasts, and these features tend to mediate reshaping of the TME and ultimately impact cancer evolution . CAFs have an active role in mutual bidirectional interactions with tumor cells and other cell types in the TME, thereby promoting the niche that allows the tumor and promoting tumor development.…”
Section: Introductionmentioning
confidence: 62%
“…We previously demonstrated that CAFs reactivity is crucial to induce an epithelial to mesenchymal transition (EMT) of PC-3 cells gaining them with pro-invasive capabilities [14,29,30]. Thus, to evaluate if cannabinoids could affect also the pro-invasive activity of CAFs, PC-3 cells were exposed for 48 h to the conditioned media obtained from CAFs treated or not with cannabinoids.…”
Section: Win 55-2122 Mesylate Impacts On Cafs Phenotype and Impairs mentioning
confidence: 99%
“…This includes a shift of CAFs metabolism toward glycolysis with accelerated expression of glucose transporter GLUT1 and increased lactic acid production and secretion. In turn, CAF-generated lactate stimulates mitochondrial biogenesis and aerobic metabolism in PCa cells (reverse Warburg effect) associated with a decrease in expression of GLUT1 transporter and activation of lactate upload [117][118][119][120]. Notably, lactate-mediated tumor acidification has been associated with suppression of anticancer immune response mediated by the loss of cytotoxic T-cell and NK cell function, reduction of dendritic cell maturation and increased helper cell activities as reviewed by Choi and coauthors [121].…”
Section: Pcsc Nichementioning
confidence: 99%